2022
DOI: 10.1093/plcell/koac089
|View full text |Cite
|
Sign up to set email alerts
|

Out of the blue: Phototropins of the leaf vascular bundle sheath mediate the regulation of leaf hydraulic conductance by blue light

Abstract: The Arabidopsis (Arabidopsis thaliana) leaf veins bundle sheath cells (BSCs) – a selective barrier to water and solutes entering the mesophyll – increase the leaf radial hydraulic conductance (Kleaf) by acidifying the xylem sap by their plasma membrane H+-ATPase, AHA2. Based on this and on the BSCs’ expression of phototropins PHOT1 and PHOT2, and the known blue-light (BL)-induced Kleaf increase, we hypothesized that, resembling the guard cells, BL perception by the BSCs’ phots activates its H+-ATPase, which, c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(43 citation statements)
references
References 68 publications
7
34
0
Order By: Relevance
“…6). It is interesting to note that similarities between the regulation mechanisms of guard cells and BSC have also been reported in the context of blue light signal-transduction pathways, which initiate stomatal opening while increasing bundle sheath Pf (Iino et al, 1985;Zait et al, 2017;Torne et al, 2021;Grunwald, 2022). Our findings also reinforce the importance of the BSC as a leaf hydraulic checkpoint (Ache et al, 2010;Griffiths et al, 2013;Caringella et al, 2015).…”
Section: Bsc and MC Control Kleaf And Transpiration Via Aba Regulationsupporting
confidence: 82%
“…6). It is interesting to note that similarities between the regulation mechanisms of guard cells and BSC have also been reported in the context of blue light signal-transduction pathways, which initiate stomatal opening while increasing bundle sheath Pf (Iino et al, 1985;Zait et al, 2017;Torne et al, 2021;Grunwald, 2022). Our findings also reinforce the importance of the BSC as a leaf hydraulic checkpoint (Ache et al, 2010;Griffiths et al, 2013;Caringella et al, 2015).…”
Section: Bsc and MC Control Kleaf And Transpiration Via Aba Regulationsupporting
confidence: 82%
“…7). Based on our earlier demonstration of the AHA2's prominent role in the leaf xylem sap acidification (Grunwald et al, 2021(Grunwald et al, , 2022, we now identify AHA2 as the BSCs-specific target of the ABA-inducible signaling cascade. This resembles the Arabidopsis seedlings hypocotyl (Hayashi et al, 2014) 2D-2F).…”
Section: Bl-induced Activation Of Aha Via Elevated [Ca 2+mentioning
confidence: 94%
“…Together, these results demonstrated that the BSCs’ external pH (pH EXT ) affected K leaf by regulating the individual BSCs’ P f (Grunwald et al, 2021). Our finding that pH EXT mediated the promoting effect of BL on the BSCs P f and through this – on K leaf (Grunwald et al, 2022), invited a question whether pH EXT mediated also the above-mentioned inhibitory effects of ABA on both the BSCs’ P f and K leaf (Shatil-Cohen et al, 2011). Furthermore, since aquaporins are reportedly inhibited by low cytosolic pH (Tournaire-Roux et al, 2003) we wondered whether the inhibitory effects of ABA on K leaf involved also the acidification of the BSCs cytosol.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations